1969
DOI: 10.1021/jf60164a043
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic pathways affecting toxicity of N-acetyl Zectran

Abstract: A-Acetylation of the insecticide Zectran does not greatly alter its toxic effects on spruce budworm, but virtually eliminates toxicity in mice. The fate of acetylated Zectran was investigated by using several radioactive labels. Mice detoxify acetyl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1970
1970
1999
1999

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Alterations in physical properties and partitioning characteristics on derivatization might contribute to the changes in biological activity. There is already speculation and evidence from studies with iV-phosphorothioyl and N-acetyl derivatives that the carbamate ester moiety may be preferentially cleaved in mammals leading to detoxification, while the phosphorothioyl or acetyl group is more readily removed by insects yielding the toxic N-methylcarbamates (Fahmy et ai, 1970;Miskus et al, 1969). A third hypothesis, involving interaction of the derivatizing group with the microsome mixed-function oxidase system, is also worthy of consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in physical properties and partitioning characteristics on derivatization might contribute to the changes in biological activity. There is already speculation and evidence from studies with iV-phosphorothioyl and N-acetyl derivatives that the carbamate ester moiety may be preferentially cleaved in mammals leading to detoxification, while the phosphorothioyl or acetyl group is more readily removed by insects yielding the toxic N-methylcarbamates (Fahmy et ai, 1970;Miskus et al, 1969). A third hypothesis, involving interaction of the derivatizing group with the microsome mixed-function oxidase system, is also worthy of consideration.…”
Section: Discussionmentioning
confidence: 99%
“…With this rationale in mind, it was anticipated that substitution of the proton on the vV-methyl moiety of carbamate esters, which are toxic to both mammals and insects, by a substituted phosphorothioyl group might give compounds of reduced mammalian toxicity, owing to the possibilities for alternate routes of detoxication in mammals and insects. Recently, Miskus et al (1969) showed the IV-acetyl Zectran (4-dimethylamino-3,5-xylyl A-acetyl-TV-methylcarbamate), a derivative of Zectran which is toxic to the spruce budworm but of low toxicity to mice, is metabolized in this insect into relatively large amounts of the carbamate Zectran, but is detoxified by mice through hydrolysis of the carbamate ester moiety to the nontoxic product 4-dimethylamino-3,5-xylenol. This paper represents part of our continuing endeavor to design molecules which will be selectively toxic to insects, and specifically is concerned with the insecticidal and mammalian toxicity of a series of vV-(dialkylphosphorothioyl) derivatives of commercially important methylcarbamate insecticides.…”
mentioning
confidence: 99%
“…Studies on the metabolism and mode of action of derivatized methylcarbamate esters have shown that their lower mammalian toxicities are attributable to the preferential metabolic detoxication of the derivatives to nontoxic products (Black et al, 1973;Miskus et al, 1969;Krieger et al, 1976;Fahmy et al, 1978). In the target species, however, in the case of the formamidine-S-carbamate, the active methylcarbamate as well as the formamidine is most likely generated in vivo, resulting in intoxication.…”
Section: Discussionmentioning
confidence: 99%